The Garpu Banting-Women’s Movement Program Prevent Stunting Increases Knowledge of Feeding Practices: Quasi-Experiment - Annisa, Lulu; Ismail, Djauhar; Sulistyaningsih, Sulistyaningsih (Poltekkes Kemenkes Palu, 2025)
Background: The prevalence of stunting in Indonesia in 2022 was 21.6%, stunting can cause cognitive impairment, short stature, pain and even death. The aim is to determine the effect of the Garpu Banting Program on the mothers’ level of knowledge, attitudes, and practices in feeding. Methods: This study used a quasi-experimental design with pre-test, post-test and control group designs.The Sampling used experimental research standards (CONSORT) with a sample size of 50, namely 25 in the experimental group and 25 samples in the control group. Results: The findings revealed variations in the experimental group’s mothers’ knowledge (p=0.000), attitudes (p=0.000), and practices (p=0.000) regarding feeding before and after receiving the Garpu Banting Program’s nutrition education and home visits. In the control group, there were differences in the mean ratings of mothers' feeding knowledge (p=0.000), attitude (p=0.000), and practice (p=0.009). Logistic regression analysis found that education (OR=10.630 (0.820-0.140), source of information (OR=0.673 (0.177-2.555), and employment (OR=3.781 (0.754-18.949)) did not influence on mothers’ attitudes and practices in feeding. Conclusion: The Garpu Banting Program has a considerable impact on mothers’ knowledge, attitudes, and feeding patterns through nutritional education on complementary foods and home visits.